The Effects of Distinct Learning Models and Techniques on The Online Educationof Adults - Zainub Hayat; Muhammad Jibran (Spectrum of Engineering Sciences, 2024)
The purpose of this study was to investigate the ways in which the degree of computer skills, preferred learning styles, and prior experience with online courses influenced the acquisition of knowledge among adult learners who were participating in an online special educationcourse. There were a total of forty-six adult students that participated in the research project andregistered for a special education course that was offered online. Based on the findings of thestudy, it was discovered that the learning styles and preferences of adult students haveasubstantial impact on their knowledge acquisition. Additionally, the study discovered that computer proficiency has a moderately positive link with academic achievement. Duringthecourse of the research, it was discovered that there was no substantial connectionbetweenprevious involvement in online courses and achievement in web-based courses. Keywords: Web-based learning, learning styles, computer skills, adult learners